(untitled) (Journal of Numerical Optimization and Technology Management, 2024)
The main purpose of this study is to apply parametric techniques in evaluating the technical efficiency (TE) of crude palm oil (CPO) production by the states in Malaysia. To achieve this, the parametric stochastic frontier analysis (SFA) approach was applied. This study involves a panel data consisting of 12 CPO producing states in Malaysia, over a 18 year time period from year 1999 to 2016. The output variable chosen was the annual CPO production and the input variables considered were plantation area, fruit mill capacity, labour and time variable. We found fruit mill capacity, labour and time as input variables that significantly affect the level of CPO output. Plantation area was proven to be statistically insignificant. Technical efficiency was found to be increasing over time. It was also found that the inefficiencies in the industry were mainly caused by ‘pure’ technical inefficiency rather than scale inefficiency. The overall mean TE of SFA is 0.79. Selangor is the top efficient state according to SFA. We concluded that the state of Malacca is overall the least efficient state due to their low ranking.